Sinergitas Pendampingan Ekonomi Usaha Mikro Di Lembaga Amil Zakat Dārut Tauhīd Provinsi Jambi - Muhammad Absor; Ahmad Syukri; Bahrul Ma’ani (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to examine the management of micro business assistance at the national zakat institution (LAZNAS) Dārut Tauhīd, Jambi province, and what inhibiting and supporting factors are faced by mentors and micro business beneficiaries, as well as what efforts have been carried out by the Darut Amil Zakat institution Monotheism in mentoring. The use of this research is to provide an evaluation of the program that has been carried out so far by the national amil zakat institution (LAZNAS) Dārut Tauhīd caring for Jambi as well as as input and suggestions so that the implementation of assistance in the future will be even better. This research is qualitative research with a method using a descriptive approach, where data is collected using interview, observation and documentation techniques